Ileal Perforation with Norovirus Gastroenteritis in a 3-Month-Old Infant - Wi, Seol Woo; Lee, Su Jin; Kang, Eun Kyeong; Cho, Sung Min (Pediatric gastroenterology, hepatology & nutrition, 2017)
Noroviruses have been recognized as the leading cause of epidemic and sporadic gastroenteritis since the advent of molecular diagnostic technique. They have been documented in 5-31% of pediatric patients hospitalized with gastroenteritis. Although norovirus gastroenteritis is typically mild and self-limited, it causes severe, but sometimes fatal, conditions in the vulnerable population such as immunocompromised patients, young children, and the elderly. Bowel perforation due to norovirus infection is rare. We report a case of small bowel perforation with norovirus gastroenteritis in the infant with Down syndrome during the hospitalization with pneumonia. Severe dehydration may cause bowel ischemia and could have triggered bowel perforation in this case. Physicians should be alert to the potential surgical complications followed by severe acute diarrhea, especially in high risk groups.